2004
DOI: 10.1149/1.1819837
|View full text |Cite
|
Sign up to set email alerts
|

Direct Methanol Fuel Cell Performance of Disulfonated Poly(arylene ether benzonitrile) Copolymers

Abstract: This paper reports the performance of direct methanol fuel cells ͑DMFCs͒ using novel disulfonated poly͑arylene ether benzoni-trile͒ copolymers derived from hexafluoro-isopropylidene diphenol ͑6F͒, 2,6-dichlorobenzonitrile, and 3,3Ј-disulfonated 4,4Ј-dichloro diphenyl sulfone ͑SDCDPS͒. The membrane electrode assembly ͑MEA͒ which employed the sulfonated copolymer with 35 mol % of disulfonated comonomer as the proton exchange membrane had approximately 2-fold lower methanol crossover and slightly higher ͑about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 25 publications
4
115
0
Order By: Relevance
“…Similar to our finding, Kim et al investigated surface fluorine enrichment in the 6FCN-35 membranes [52], i.e., disulfonated poly(arylene ether benzonitrile) copolymers containing hexafluoroisopropylidene diphenol, whose molar ratio of unsulfonated benzonitrile to the disulfonated sulfone monomer was 65:35. They also found that surface fluorine, lower surface energy group, was enriched on the air-contacting surface to about 38%, doubling the 17% of fluorine content of the bulk membrane.…”
Section: Surface Behavior Of Copolymer Speek-hq Membranesupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our finding, Kim et al investigated surface fluorine enrichment in the 6FCN-35 membranes [52], i.e., disulfonated poly(arylene ether benzonitrile) copolymers containing hexafluoroisopropylidene diphenol, whose molar ratio of unsulfonated benzonitrile to the disulfonated sulfone monomer was 65:35. They also found that surface fluorine, lower surface energy group, was enriched on the air-contacting surface to about 38%, doubling the 17% of fluorine content of the bulk membrane.…”
Section: Surface Behavior Of Copolymer Speek-hq Membranesupporting
confidence: 88%
“…The glass-contact surface was found to have close to unchanged fluorine content about 15%. The differences of fluorine atomic concentration on different sides of a membrane were attributed to the low surface free energy of the hexafluoroisopropylidene moiety, which provided a thermodynamic driving force for the selfassembly at the air-polymer interface, leading to fluorine hydrophobic groups enrichment, on the air-contacting membrane surface [52]. In this study the information about the membrane surface within less than 1 µm was investigated using ATR-FTIR (Fig.…”
Section: Surface Behavior Of Copolymer Speek-hq Membranementioning
confidence: 99%
“…Although this is outside the scope of this paper, there are a few references in this regard [60,61]. Improved DMFC performance is then anticipated with a well-designed DMFC PEMs [62,63].…”
Section: Molecular Design and Optimization Of Dmfc Pemsmentioning
confidence: 99%
“…DMFC MEA fabrication and fuel cell operating conditions were conducted according to a reported procedure [3,5]. The anode ink composition was 86 wt% 1:1 platinum-ruthenium (Johnson Matthey) and 14 wt% Nafion ® , and the cathode ink composition was 90 wt% platinum black (Johnson Matthey) and 10 wt% Nafion ® .…”
Section: Mea Fabrication and Testmentioning
confidence: 99%
“…Known for their outstanding chemical, mechanical and oxidative stability and high proton conductivity, perfluorinated sulfonic acid polymers (such as Nafion ® ) exhibit excellent electrochemical performance as polymer electrolyte membranes (PEMs). To date, only a few PEMs have been reported to possess improved single cell performance over commercial Nafion ® -type PEMs [3][4][5][6][7]. As an example, the PEMs based on stretched recast Nafion ® were claimed to have better performance than commercial Nafion ® in DMFCs [6,7].…”
Section: Introductionmentioning
confidence: 99%